TINA EVANS’S DEPRESSION IN DEAN KOONTZ’S THE EYES OF DARKNESS - Yuni Sulistiyo Rahmawati; Danu Wahyono (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2022)
This study analyzes the depression experienced by Tina Evans in the novel The Eyes of Darkness written by Dean Koontz. The focus of this research is the symptoms of depression experienced by Tina Evans, the causes and effects of depression experienced by Tina Evans, and the last is the solution to the depression experienced by Tina Evans. This study uses a qualitative method. This research is conducted by applying a psychological approach. From this analysis, it can be concluded that there are two symptoms of depression experienced by Tina Evans, namely sadness and sleep disturbances. The causes of Tina's depression are the stress of losing a loved one; her marital status is due to her husband Michael Evans' affair, which ended in their divorce, the third cause is trauma, and the last cause is spiritual terror experienced by Tina Evans. From the causes of depression experienced by Tina Evans, there are three effects of depression: insomnia, lack of concentration, and nightmares. The final discussion of this research is the solution to depression or how Tina Evans overcomes her depression. In the end, Tina manages to overcome her depression in various ways. From the results of the analysis, it is known that there are six solutions that Tina Evans do in overcoming her depression; namely, the first to distract her mind with hard work, the second to take significant responsibility for her work, the third to try to divert her mind by consuming alcohol, the fourth to think positively about whatever is happens she experienced, the fifth is expressing herself to talk to other people, in this case, Tina is trying to open up to her boyfriend. The last one is to accept the spiritual terror that is haunting her and find the facts about the death of her son Danny Evans with the help of Elliot Stryker. At the end of this analysis is Tina Evans, who overcame her depression by finding Danny Evans alive and back in her arms.